How therapist self-disclosure relates to alliance and outcomes: A naturalistic study. Issue 1 (2nd January 2016) - Levitt, Heidi M.; Minami, Takuya; Greenspan, Scott B.; Puckett, Jae A.; Henretty, Jennifer R.; Reich, Catherine M.; Berman, Jeffery S.
Abstract : This study examined therapists' self-disclosure within early sessions of a naturalistic database of 52 therapy dyads collected at a university counseling center. Therapist orientations and client issues varied. We identified both types and functions of therapist self-disclosure in order to explore how self-disclosures related to therapy alliance and outcomes. Findings indicated that the number of disclosures was not significantly correlated with outcome or alliance scores. Central findings regarding the function of self-disclosures included that disclosures that acted to humanize the therapist were associated with fewer clinical symptoms post-session than disclosures expressing appreciation or encouragement. Also, disclosures that conveyed similarity between the therapist and client were associated with fewer post-session clinical symptoms and interpersonal problems when compared to disclosures that conveyed neither similarity nor dissimilarity. As well, neutral therapist self-disclosures were associated with better client functioning than disclosures that relayed negative or positive information about the therapist. Suggestions are provided for clinical practice and future research.